The whisking hour - Alexander, Ellie (Alexander, Ellie. Bakeshop mystery, 2026)
"Fall is in full flush in the charming hamlet of Ashland, Oregon, and baker Juliet Capshaw is excited to celebrate the season with a night at the theatre. Lance Rousseau, Ashland's renowned theater director and one of Jules' closest friends, has put his own spin on a production of the Broadway classic Perfect Crime, drawing the audience into a cozy New York apartment as a nefarious set of suspects pulls off the perfect murder. As the final show approaches, Jules and the team at Torte are eagerly whipping up a murderous feast for the cast party, baking a bevy of treats like panna cotta eyeballs with blood orange coulis, deviled eggs, and savory cheese fingers with pumpkin dipping sauce. On the day of the soirée, life seems to imitate art when a storm rolls over the Siskiyou Mountains, ushering in gusty winds and unrelenting rain. The audience buzzes with electric energy as the lights flicker and the actors take the stage. After the actors take their final bow, the cast trickles into Carpenter Hall, ready for a night of frivolity. But when an actor is discovered dead in his dressing room, Jules wonders if she's just witnessed the real perfect murder."--Amazon.